2013
DOI: 10.1310/sci1904-279
|View full text |Cite
|
Sign up to set email alerts
|

Restoring Voluntary Grasping Function in Individuals with Incomplete Chronic Spinal Cord Injury: Pilot Study

Abstract: The results of the pilot data justify a clinical trial to compare FES therapy and COT alone to improve voluntary hand function in individuals with chronic incomplete tetraplegia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 29 publications
(48 reference statements)
2
50
0
Order By: Relevance
“…They used a neuroprotesis with electrodes implanted in the upper limb muscles to create and assist on movements by FES. Kapadia et al (2013) used the Compex Motion Stimulator (FES) to restore eight tetraplegics in the subacute phase. Two groups were formed: occupational therapy exercises (control) and FES therapy (intervention).…”
Section: Discussionmentioning
confidence: 99%
“…They used a neuroprotesis with electrodes implanted in the upper limb muscles to create and assist on movements by FES. Kapadia et al (2013) used the Compex Motion Stimulator (FES) to restore eight tetraplegics in the subacute phase. Two groups were formed: occupational therapy exercises (control) and FES therapy (intervention).…”
Section: Discussionmentioning
confidence: 99%
“…Two of the selected studies were small, randomized controlled trials with measurements prior to commencing therapy and completion of therapy [13,14]. Applying the Jovell and Novarro-Rubio [12] classification, a methodological score of III was assigned.…”
Section: Methodological Quality Judgementmentioning
confidence: 99%
“…All five studies reported improvement, both immediate and at follow-up, in motor control and/or functional ability of upper extremity as a result of FES or FES with conventional therapy (Table 3) [13][14][15][16][17].…”
Section: Study Outcomesmentioning
confidence: 99%
“…Trained subjects had significant increases in total motor scores and lower extremity motor scores, as well as walking speeds, and total distances walked. Kapadia et al (129) studied eight participants with subacute cervical SCI. Five received 39 h of FES training of hand function over 13-16 weeks and three did not.…”
Section: Peripheral Nerve Stimulationmentioning
confidence: 99%
“…Many clinical studies suggest that both central and peripheral electrical stimulation improve long-term motor (90) and sensory recovery (204), including standing (48), walking (96,105,130,204), and hand function (106,129).…”
Section: Introductionmentioning
confidence: 99%